Price as a Stimulus to Think: The Case for Willful Overpricing - Wathieu, Luc; Bertini, Marco (Marketing Science, 2007)
Consumers aware of a new benefit will often experience uncertainty about its personal relevance or usage value. This paper shows that the decision to deliberate further to resolve this uncertainty and reach a polarized judgment of personal relevance critically depends on the posted price. In particular, a price above the consumer’s initial willingness to pay might be thought provoking and enhance the perception of relevance with a certain probability. This behavioral mechanism is introduced formally and by way of an experiment with reference to the purchase of organic lettuce and fair-trade coffee. Accounting for the effect of price as a stimulus to think, a monopolistic firm should either over price (“transgressive pricing”) or under price (“regressive pricing”) in comparison to the consumer’s willingness to pay. Under certain circumstances, the firm should also empower consumers with means that reduce the effort of deliberation.